THE INFLUENCE OF SERVICE QUALITY, TAX KNOWLEDGE, TAX SANCTIONS, TAXPAYER AWARENESS AND TAXPAYER ENVIRONMENT ON TAXPAYER COMPLIANCE (Cases Study of Taxpayer PPH 21 of Civil Servants in Pemalang District) - Nurdhiana Nurdhiana; Triani Triani (Faculty of Economic and Business Universitas STIKUBANK, 2022)
This study aimed to examine the influence of service quality, tax knowledge, tax sanctions, and taxpayer environment on taxpayer compliance at Regional Office of Pemalang District. The total population of Civil Servantswas 9.962, the samples used in this study were 100 people. The analysis method used multiple linier regresion. According to classic assumtion test, it showed that the data valid and reliable. The result of t distribution showed service quality had t value 3,129 and more than t table (>1,985), therefore service quality had positive and significant influenceon taxpayer compliance. The result of t distribution showed tax knowledge had t value 2,891 and more than t table (>1,985), therefore tax knowledge had positive and significant influenceon taxpayer compliance. The result of t distribution showed tax sanctions had t value 2,731 and more than t table (>1,985), therefore tax sanctions had positive and significant influenceon taxpayer compliance. The result of t distribution showed taxpayer environment had t value -0,376 and less than t table (<1,985), therefore taxpayer environment didn’t influence taxpayer compliance.